Enzymatic Treatment of Cotton Fabric for Desizing - Rafikov, Adham S.; Fayzullaeva, Kamola; Shonakhunov, Tulkin E.; Soyibova, Dilnoza B. Qizi; Yasinskaya, Nataliya N. (Journal of Chemical Engineering Research Updates, 2023)
The possibility of softening the conditions of biochemical treatment to remove the sizing agent from the surface of the fibers in the preparation of cotton fabric for dyeing has been studied. The efficiency of the α-amylase enzyme was evaluated by the amount of sugars reduced in the modifying solution, as well as by the capillarity of the samples of the treated fabrics. The enzyme used is active towards starch starting from a low concentration (0.02 g/l) and low temperature (32°C). The effect of enzyme concentration from 0.02 to 6.0 g/l, solution pH from 4.5 to 8.5, temperature from 32 to 60°C on the amount of sugars in the solution after enzymatic treatment, and fabric capillarity was determined. Almost complete removal of sizing from the surface of fibers of the original fabric was achieved under moderate and mild processing conditions: α-amylase concentration 1.0÷5.0 g/l, pH=6.0÷7.0, temperature 50-55°C. Based on the dependence of the logarithm of the reaction rate on the reciprocal temperature, the activation energy of the desizing reaction was calculated, which turned out to be equal to E = 17.5 kJ/mol. The low activation energy shows that the desizing process is carried out under energetically favorable conditions with moderate heating. The surface morphology of treated and untreated samples of cotton fabric was studied by scanning electron microscopy. The removal of the adhesive substance from the surface of the fibers, the separation of individual fibers, and the smoothing of the fabric surface after treatment with an amylase solution were recorded.